KONVERSI LIMBAH PELUMAS KAPAL PERIKANAN MENJADI MINYAK MURNI DAN BAHAN BAKAR DIESEL: PROSES DAN POTENSI - Fahriadi Pakaya; Yurika Nantan; Jozua Ch Huwae; Mohamad Haris; Erick Renold Rakinaung; Aliffa Yusti Octikharisma (Jurnal Perikanan Unram, 2024)
Bitung city is one of the industrial, port, and tourist centers in North Sulawesi Province, with many fishing vessels passing through and docking in Bitung waters. Consequently, there is a potential for marine environmental pollution due to oil spills and the intentional or unintentional discharge of used oil into the sea. According to BPS data in 2022, there are approximately 1,100 fishing vessels operating in Bitung waters. Therefore, the daily demand for oil to meet the lubrication needs of main and auxiliary engines is increasing. This poses a significant environmental problem because fishing vessels in Bitung are generally not equipped with oil-water separators. The aim of this activity is to recycle used oil and refine it, while also converting the used oil into diesel fuel. The method used involves collecting used oil from fishing vessels, dissolving it with H2SO4 and NaOH, and separating it through a fractionation process to remove water molecules and heavy metals trapped in the long hydrocarbon chains of the oil. The results of the study indicate that this technology is effective in reducing contamination and producing products that meet standards. The addition of NaClO-NaOH-NaClO solution to kapok fiber enhances its hydrophilic properties, and the combination of H2SO4 and NaOH successfully binds impurities in the used oil. The use of activated charcoal effectively changes the color of the oil and removes contaminants. The recycled oil has a density of 0.837 g/cm³ and a specific gravity of 0.884, meeting the existing standards. The diesel fuel produced has a density of 0.801 g/cm³, approaching the industrial standard of 0.820 g/cm³. Thus, recycling used oil has the potential to be a suitable solution for addressing environmental issues while supporting the local economy